Numerical Study of Heat Transfer Enhancement of Turbulent Flow Using Twisted Tape Insert Fitted with Hemispherical Extruded Surface - Rubbi, F. (International Information and Engineering Technology Association, 2020)
Heat transfer enhancement of heat exchangers is an important matter of concern to achieve more effective thermal energy conversion systems. The use of modified twisted tape (TT) inserts as passive technique of heat transfer augmentation are effective way to improve heat transfer. In this study, a numerical analysis is performed to investigate the heat transfer performance enhancement and flow behavior in a circular pipe using TT insert fitted with a hemispherical extruded surface (HES). The study is carried out for the turbulent flow regime (4000â¤Reâ¤10000) at a twist ratio of 4.0 using ANSYS FLUENT. A flow domain is designed and mathematically modeled applying boundary conditions and using governing equations for turbulent model. The plain tube data is validated with established correlations. The achieved numerical results reveal that for TT fitted with HES leads to increment in heat transfer rate up to 69.4 compared to plain tube due to effective swirl flow and better mixing caused by the insert. Corresponding increase in friction factor is found relative to plain tube. The impact on the thermal performance factor has obtained a maximum of 1.24 at constant pumping power for Reynold number 4000. Â© 2020 International Information and Engineering Technology Association. All rights reserved.